A Novel Microtubule-Binding Drug Attenuates and Reverses Protein Aggregation in Animal Models of Alzheimer’s Disease - Kakraba, Samuel; Ayyadevara, Srinivas; Penthala, Narsimha Reddy; Balasubramaniam, Meenakshisundaram; Ganne, Akshatha; Liu, Ling; Alla, Ramani; Bommagani, Shoban Babu; Barger, Steven W.; Griffin, W. Sue T.; Crooks, Peter A.; Shmookler Reis, Robert J. (Frontiers in Molecular Neuroscience, 2019)
Age-progressive neurodegenerative pathologies, including Alzheimer’s disease, are distinguished and diagnosed by disease-specific components of intra- or extra-cellular aggregates. Increasing evidence suggests that neuroinflammation promotes protein aggregation, and is involved in the etiology of neurological diseases. We synthesized and tested analogues of the naturally occurring tubulin-binding compound, combretastatin A-4. One such analogue, PNR502, markedly reduced the quantity of Alzheimer-associated amyloid aggregates in the BRI-Aβ1–42 mouse model of Alzheimer’s disease, while blunting the ability of the pro-¬inflammatory cytokine IL-1β to raise levels of amyloid plaque and its protein precursors in a neuronal cell-culture model. In transgenic C. elegans strains that express human Aβ1–42 in muscle or neurons, PNR502 rescued Aβ-induced disruption of motility (3.8-fold, P<0.0001) or chemotaxis (1.8-fold, P<0.05), respectively. Moreover, in C. elegans with neuronal expression of Aβ1–42, a single day of PNR502 exposure reverses the chemotaxis deficit by 54% (P<0.01), actually exceeding the protection from longer exposure. Moreover, continuous PNR502 treatment extends nematode lifespan 23% (P≤0.001). Given that PNR502 can slow, prevent, or reverse Alzheimer-like protein aggregation in human-cell-culture and animal models, and that its principal predicted and observed binding targets are proteins previously implicated in Alzheimer’s, we propose that PNR502 has therapeutic potential to inhibit cerebral Aβ1–42 aggregation and prevent or reverse neurodegeneration.